2017
DOI: 10.2299/jsp.21.195
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D Mesh Watermarking Scheme with Highpass Filter

Abstract: In this paper, we investigate a blind watermarking algorithm based on a highpass filter for three-dimensional (3-D) meshes. For improving watermark detection in correlationbased watermarking, our scheme employs the highpass filter which emphasizes an impulse signal embedded as a signature into a host mesh. In the proposed method, we align the host mesh by the principal component analysis and convert from orthogonal coordinates to polar coordinates. After this preprocessing, we map the 3-D data onto a 2-D space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The proposed scheme was compared with two other representative schemes (Taniguchi & Uto, 2017; Wang et al., 2018) in terms of the coordinate errors after information embedding. Looking at the error statistics data in Table 3, it can be observed that the Root Mean Square Error and Maximum Error for the four models after embedding fingerprint information in the proposed scheme are both less than 0.00001.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…The proposed scheme was compared with two other representative schemes (Taniguchi & Uto, 2017; Wang et al., 2018) in terms of the coordinate errors after information embedding. Looking at the error statistics data in Table 3, it can be observed that the Root Mean Square Error and Maximum Error for the four models after embedding fingerprint information in the proposed scheme are both less than 0.00001.…”
Section: Experiments and Analysismentioning
confidence: 99%